Investigation of the Low-Temperature Behavior of FD-SOI MOSFETs in the Saturation Regime Using Y and Z Functions - A. Karsenty; A. Chelly (Active and Passive Electronic Components)
The saturation regime of two types of fully depleted (FD) SOI MOSFET devices was studied. Ultrathin body (UTB) and gate recessed channel (GRC) devices were fabricated simultaneously on the same silicon wafer through a selective “gate recessed” process. They share the same W/L ratio but have a channel film thickness of 46 nm and 2.2 nm, respectively. Their standard characteristics (IDS-VDS and IDS-VGS) of the devices were measured at room temperature before cooling down to 77 K. Surprisingly, their respective temperature dependence is found to be opposite. In this paper, we focus our comparative analysis on the devices' conduction using a Y-function applied to the saturation domain. The influence of the temperature in this domain is presented for the first time. We point out the limits of the Y-function analysis and show that a new function called Z can be used to extract the series resistance in the saturation regime.